2020
DOI: 10.1016/j.petrol.2020.107940
|View full text |Cite
|
Sign up to set email alerts
|

Static fatigue of saline rocks under different CO2 phase conditions

Abstract: Static fatigue tests were conducted on core samples saturated with different phase CO2 to evaluate the fatigue rate and bulk modulus under constant but stepped stress increment. There was re-appearance of primary fatigue at higher stress in all the samples. In the brine saturated sample, for a 4 MPa deviatoric stress increase, there was about 89% increase in primary fatigue rate with up to 16% more strain, up to 88% reduction in fatigue rate when fatigue goes from primary to secondary fatigue and a reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Dissolution of CO 2 in brine produces an acidic solution. Results from Peter et al (2020), Pimienta et al (2017) and Zou et al (2018) show that the impact of CO 2 on the properties of rock starts vigorously almost immediately. Hence, for this experiment, any duration greater than 5 days is considered sufficient for the phaseCO 2 -brine to have an effect on the rock properties.…”
Section: Experimental Set Up and Proceduresmentioning
confidence: 98%
“…Dissolution of CO 2 in brine produces an acidic solution. Results from Peter et al (2020), Pimienta et al (2017) and Zou et al (2018) show that the impact of CO 2 on the properties of rock starts vigorously almost immediately. Hence, for this experiment, any duration greater than 5 days is considered sufficient for the phaseCO 2 -brine to have an effect on the rock properties.…”
Section: Experimental Set Up and Proceduresmentioning
confidence: 98%
“…Li et al (2019) reported that the effect of CO2 on the properties of rocks increase with longer exposure time. Results from Peter et al (2020); Pimienta et al (2017); Zou et al (2018) and Olabode and Radonjic (2013) showed that CO2-brine causes marked effects on rock properties even within a short contact period and the severity increases over time. Pimienta et al (2017) had used 2 and 4 hours exposure time; Zou et al (2018) had used 0.5 hour exposure time and Li et al (2019) had used a maximum of 168 hours.…”
Section: Previous Workmentioning
confidence: 98%
“…They all had significant changes in properties. Peter et al (2020), reported that excess of 5 days is good enough for CO2-brine to affect the properties of the rocks. Therefore, it was decided that for this experiment, more than of 5 days would be good enough for the phaseCO2 saturated-brine to have an effect on the properties of the rocks.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations